Analisis Tingkat Pengetahuan Taktik dan Strategi Futsal pada Pemain Ekstrakurikuler SMAN 2 Kerinci - Tuqya, Habil; Munar, Hendri; Yanto, Anggel Hardi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This research was conducted to identify the extent of understanding of futsal strategies and tactics among students participating in futsal extracurricular activities at SMAN 2 Kerinci. The approach used was a quantitative descriptive method through a questionnaire instrument containing 47 statement items. The study population included all 20 members of futsal extracurricular at SMAN 2 Kerinci with the application of total sampling technique. Data processing was carried out using descriptive statistics and percentage analysis. Findings indicate that understanding of futsal strategies and tactics among SMAN 2 Kerinci extracurricular students falls into the adequate category with an average score of 26. The distribution of results shows no students (0%) in the very weak category, 45% in the weak category, 5% in the adequate category, 50% in the good category, and none (0%) in the very good category.